Empowered Vulnerable Groups: How Digital Media Portrays The Vulnerable Group In Indonesia Within Its Content - Nindita Asrining Tisna; Sarah Derma Ekaputri (Interaksi: Jurnal Ilmu Komunikasi, 2026)
This study aims to analyze how the digital media outlet Narasi Newsroom, through its People segment, constructs the image of vulnerable groups within the context of social life. Vulnerable groups in this research include women, the elderly, indigenous communities, the poor, and communities with diverse social identities. This study employs a qualitative content analysis with a descriptive approach, using Peter L. Berger's theory of the social construction of reality as the analytical framework. The results show that Narasi Newsroom presents vulnerable groups as individuals and communities with roles, values, and sociocultural strengths worthy of recognition. Through the use of symbols, narratives, and depictions of daily activities, these groups are portrayed not merely as victims, but as active members of society with social roles. The media thus facilitates a social construction process that encourages a more positive public perception of vulnerable communities. This research recommends the importance of a journalistic approach that involves the subjects directly in the media coverage, so that vulnerable groups are given space to express their identities and life values in a complete and dignified manner.